2001
DOI: 10.1002/j.2048-7940.2001.tb01946.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Disease-Modifying Therapy in Multiple Sclerosis: Part I

Abstract: Multiple sclerosis (MS) is a chronic, debilitating disease for which there is no cure. However, the recent introduction of injectable immunomodulating agents has made it possible to reduce the frequency of relapsing episodes and to possibly slow its progression. The use of these agents is recommended by the National MS Society, however, their true potential cannot be realized if patients do not accept them and healthcare professionals do not promote them. Because MS is unpredictable, and treatments can produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…Current disease-modifying treatments for MS must be injected, posing special challenges regarding adherence. Injection anxiety is common [13,14] and physical limitations such as poor eye-hand coordination or tremor can make injections difficult to self-administer [15]. In retrospective studies of long-term adherence to betainterferon therapy, continuous therapy was achieved by only 67 [16] to 72% of patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…Current disease-modifying treatments for MS must be injected, posing special challenges regarding adherence. Injection anxiety is common [13,14] and physical limitations such as poor eye-hand coordination or tremor can make injections difficult to self-administer [15]. In retrospective studies of long-term adherence to betainterferon therapy, continuous therapy was achieved by only 67 [16] to 72% of patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that DMT might not be effective in those patients with a poor level of adherence in the long term [2]. According to different authors, the main factors that contribute to whether the patient is adherent are related to perceived lack of efficacy, lack of information or too complex information, false hopes of improvement in the disease, problems administering treatment (such as fear of needles or self-injections) and sociocultural factors [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…En revanche, la conviction du patient de réaliser correctement l'injection est un facteur de bonne observance. Il n'est pas étonnant alors que le soutien à domicile en début de traitement, qui permet notamment au patient d'apprendre les gestes nécessaires à la préparation et à l'injection à domicile [3], contribue également à une meilleure observance. Notre étude a recruté des patients initialement volontaires pour l'auto-injection.…”
Section: Discussionunclassified